Answer:
0.05 I hope that's correct:)
Answer:
8:16
Step-by-step explanation:
Answer:
y - 6 = -4(x+1) is equivalent to equation C: y = -4x + 2
Step-by-step explanation:
Solve the given y - 6 = -4(x+1) for y and remove the parentheses shown:
y - 6 = -4(x+1) becomes
y = -4(x + 1) + 6, or
y = -4x - 4 + 6, or
y = -4x + 2 This is equivalent to equation C.
Answer:
39 men, 13 women
Step-by-step explanation:
you're saying you just need the answer so i hope this works. good luck :)
Answer:
33/10
Step-by-step explanation:
I used a calculator sorry if I am wrong